Improving Quran Reading Skills with the Al-Baghdadi Method at the Muhammadiyah Blawong 1 Elementary School Yogyakarta - Santoso, Dimas Urip (TOFEDU: The Future of Education Journal, 2025)
The education system in Indonesia, especially Islamic education, issues a program every semester that must be taken by students, in the research at the elementary school, namely SD Muhammadiyah Blawong | Yogyakarta there is a program to read the Qur'an, then the researcher chose the Al-Baghdadi method by means of recognizing hijaiyah letters, conjunctions and how to recite them. This type of research is carried out by means of "classroom action research or action research. Techniques in data collection by conducting observations, interviews, tests (pretest and post-test) and field notes. The primary source in this research is the 2nd grade student of Uthman Bin Affan SD Muhammadiyah Blawong | Yogyakarta. The results of this study show (1) The ability of students before using the Al-Baghdadi method is carried out by a test or pretest (2) The learning results after using the Al-Baghdadi method have been found that the Al-Baghdadi method provides ease of learning to read the Qur'an with the achievement of the indicators obtained (3) Supporting and inhibiting factors in learning the Qur'an with the Al-Baghdadi method are adequate infrastructure, rewards for students, while the inhibiting factors are due to lack of learning concentration, classroom conditions and learning time.